Detection of Extended Spectrum Beta-lactamase gene production by E. coli isolated from human and broiler in Sulemania province/ Iraq - Saeed, Nahla M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
A total of 311 Escherichia coli isolated from 460 healthy chickens at marketing age, and 56 E. coli isolated were obtained from 124 adult workers in broiler farms between April and October 2013 -. Isolated E. coli were identified by cultural, biochemical, and Api E 20 test. Antimicrobial susceptibility testing was determined by using the modified Kirby-Bauer’s disc diffusion method. The antibiotic sensitivity result showed that the isolates were highly resistant to Beta-lactam antibiotics. Among the 311 isolated E. coli from healthy chickens 264 (84.9%) produced Beta-lactamase, while only 35 (62. 5%) of the 56 human isolates were found to produce the enzyme. All of the 264 β-lactamase producer E. coli isolated from healthy chickens and 35 β-lactamase producer E. coli isolated from human were tested for extended spectrum - β-lactamase (ESBL) production, it was found that only 201 (76.1%) and 19 (54.3%), were ESBL producers of E. coli isolated from healthy chickens and human respectively. Plasmids were detected in all ESBL producer- E. coli (201) isolated from healthy chickens, which were highly resistant to Beta-lactam antibiotics, while plasmid was detected only in 15 (78.9%) from 19 ESBLs producer E. coli isolated from human. By transformation the extracted plasmids into E. coli DH5α; it was found that 165 (82.1%) Beta-lactamase genes from 201 isolates from healthy chickens were carried by plasmid, while 10 (66.6%) Beta-lactamase genes from 15 plasmid isolated from human were carried by plasmid. The majority of these ESBL genes (69.7%) were blaTEM and (10.9%) were blaCTX-M genes in healthy chickens, while in human the majority of ESBL genes were (60%) blaTEM and (20. %) were blaCTX-M genes. Eleven isolated from healthy chickens and one isolated from human did not contain blaTEM, blaSHV or blaCTX-M.
Keywords: E coli healthy chicken human Betalactamase ESBL gene; plasmidisolation